Concentrations of essential and toxic elements and health risk assessment in brown rice from Qatari market. (15th May 2022) - Shraim, Amjad M.; Ahmad, Mohammad I.; Rahman, Mohammad Sulaiman F.; Ng, Jack C.
Graphical abstract: Highlights: Many brown rice samples contained hazardous concentrations of arsenic and cadmium. Concentration of toxic elements in brown rice is grain-size dependent. Sum of non-carcinogenic risk associated with As and other elements exceeds unity. Carcinogenic risk from As or Cr in brown rice may be as high as one in every 10, 000. Results can inform the national monitoring program for rice quality and type. Abstract: Twenty-two brown rice varieties available in the Qatari market were analyzed for essential and toxic elements by ICP-MS. Found concentrations (µg/kg) were: As: 171 ± 78 (62–343), Cd: 42 ± 60 (4–253), Cr: 515 ± 69 (401–639), Pb: 6 ± 7 (<MDL-26), and U: 0.1 ± 0.5 (<MDL-2). One third of the samples contained high levels of arsenic. Significant differences ( p < 0.008) in concentrations were observed for many elements based on both the grains' country of origin and size. Calculated carcinogenic risk according to published speciation data of inorganic arsenic and chromium(VI) available in the literature for rice is > 1 in million, may possibly be > 1 in 10, 000 based on conservatively high brown rice consumption rates of 200 g/d or 400 g/d in Qatar. These elevated risks may be applicable to specific population subgroups with diabetic conditions who consume only brown rice. Non-cancer risks are mainly derived from Mn, V, Se, and Cd with a hazard index > 1 from some brown rice samples.